Strengthening paediatric competencies and educational skills among general paediatricians. (11th May 2021) - Wekell, Per; Kullberg‐Lindh, Carola; Vallo Hult, Helena; Velander, Helena; Holmgren, Daniel
Abstract: Aim: To develop a coherent programme that addresses the need for continuing professional development in general paediatrics and educational skills for senior paediatricians at outpatient clinics in Sweden today. Methods: Educational needs in the target group were investigated using a questionnaire. Themes and sub‐themes extracted from responses informed the curriculum formulation of the continuing professional development (CPD) programme, which was completed using a variety of learning, assessment and evaluation methods. Results: Forty‐six paediatricians identified 355 clinical situations. Competencies in general paediatrics and educational skills were incorporated in a CPD programme, implemented in western Sweden between 13 October 2016 and 23 May 2019, with 23 learning modules and 18 participants (male/female 3/15, median age 55 years). The participants' evaluation emphasised the importance of adult learning principles. Their responses to open reflective questions on 23 May 2109 suggested that the programme offered a learning environment in which they could develop their paediatric and educational practices and improve their mentorship, networks and work‐based learning environment. They also described an enhanced feeling of joy at work. Conclusion: The involvement of experienced paediatricians in the programme formulation may be inspirational to clinicians and contribute to the definition, revitalisation and prioritisation of general paediatrics in Sweden in the future.